Repetitive transcranial magnetic stimulation induced modulations of resting state motor connectivity in writer's cramp. (26th January 2015) - Bharath, R. D.; Biswal, B. B.; Bhaskar, M. V.; Gohel, S.; Jhunjhunwala, K.; Panda, R.; George, L.; Gupta, A. K.; Pal, P. K.
<x xml:space="preserve">Abstract</x> Background and purpose Writer's cramp (WC) is a focal task‐specific dystonia of the hand which is increasingly being accepted as a network disorder. Non‐invasive cortical stimulation using repetitive transcranial magnetic stimulation (rTMS) has produced therapeutic benefits in some of these patients. This study aimed to visualize the motor network abnormalities in WC and also its rTMS induced modulations using resting state functional magnetic resonance imaging (rsfMRI). Methods Nineteen patients with right‐sided WC and 20 matched healthy controls (HCs) were prospectively evaluated. All patients underwent a single session of rTMS and rsfMRI was acquired before (R1) and after (R2) rTMS. Seed‐based functional connectivity analysis of several regions in the motor network was performed for HCs, R1 and R2 using SPM8 software. Thresholded (P < 0.05, false discovery rate corrected) group level mean correlation maps were used to derive significantly connected region of interest pairs. Results Writer's cramp showed a significant reduction in resting state functional connectivity in comparison with HCs involving the left cerebellum, thalamus, globus pallidus, putamen, bilateral supplementary motor area, right medial prefrontal lobe and right post central gyrus. After rTMS there was a significant increase in the contralateral resting state functional connectivity through the left thalamus−right globus pallidus−right thalamus−right prefrontal lobe network loop. Conclusions It is concluded that WC is a network disorder with widespread dysfunction much larger than clinically evident and changes induced by rTMS probably act through subcortical and trans‐hemispheric unaffected connections. Longitudinal studies with therapeutic rTMS will be required to ascertain whether such information could be used to select patients prior to rTMS therapy.